Transcriptional Analysis of Acinetobacter sp. neg1 Capable of Degrading Ochratoxin A - Liuzzi, Vania C.; Fanelli, Francesca; Tristezza, Mariana; Haidukowski, Miriam; Picardi, Ernesto; Manzari, Caterina; Lionetti, Claudia; Grieco, Francesco; Logrieco, Antonio F.; Thon, Michael R.; Pesole, Graziano; Mulè, Giuseppina (Frontiers in Microbiology, 2017)
Ochratoxin A (OTA) is a nephrotoxic and potentially carcinogenic mycotoxin produced by several species of Aspergillus and Penicillium, contaminating grapes, wine and a variety of food products. We recently isolated from OTA contaminated soil vineyard a novel free-livingstrain of Acinetobacter sp. neg1, ITEM 17016, able to degrade OTA into the nontoxic catabolic product OTalpha (OTα).Biochemical studies suggested that the degradation reaction proceeds via peptide bond hydrolysis with phenylalanine (Phe) release. In order to identify genes responsible for OTA degradation we performed a differential gene expression analysis of ITEM 17016 grown in the presence or absence of the toxin. Among the differentially expressed genes, 6 peptidases up-regulated at 6 hours were identified. The degrading activity of the carboxypeptidase PJ_1540 was confirmed in vitro in a heterologous system. The enrichment analysis for Gene Ontology terms confirmed that OTA degradation proceeds through peptidase activities and revealed the over-representation of pathways related to Phe catabolism. These results indicate that Phe may represent an energy source for this Acinetobacter sp. neg1strain and that OTA degrading reaction triggers the modulation of further catabolic activities.